La experiencia comprensiva como fundamento de una educación intercultural crítica - Merino Solari, Renatto (2015)
Since the 1990s, the discourse of interculturality has become important in thecountries of the region, to the point of achieving constitutional recognitionand presence in educational policies. This formalization interculturality makesthe challenge of sustaining the system from within the original spirit that drivestransformer. However, in our educational system it seems to dominate the useof functional interculturality that has not produced the expected changes. Thisessay argues about the possibility of returning a critical intercultural concrete fromeducation. It proposes a comprehensive experience as the founding act of thispedagogy. And it does from ideas developed education José María Arguedas